\( 3 x-20 x-35=-26.5 \) 4. Kiran and Noah are trying to solve this system by substitution: \( \left\{\begin{array}{l}2 x+y=1 \\ 2 x+7 y=19\end{array}\right. \) Kiran's first step is to isolate \( y \) in the first equation to get \( y=1-2 x \). Noah's first step is to isolate \( 2 x \) inthe first equation tege \( 3 x=1-y \). Show thaitoth first steps can be used to solve the system and will yield the same solution.
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To solve the first equation \( 2x + y = 1 \), Kiran correctly isolates \( y \) as \( y = 1 - 2x \). Substituting this into the second equation \( 2x + 7y = 19 \) gives us \( 2x + 7(1 - 2x) = 19 \). This leads to \( 2x + 7 - 14x = 19 \), simplifying to \( -12x = 12 \), resulting in \( x = -1 \) and subsequently \( y = 3 \) for a solution of \( (-1, 3) \). Noah's approach, isolating \( 2x \) from \( 2x + y = 1 \) to get \( 2x = 1 - y \), allows him to substitute into the second equation as well. Plugging \( 1 - y \) into \( 2x + 7y = 19 \) results in \( (1 - y) + 7y = 19 \). This simplifies to \( 1 + 6y = 19 \), yielding the same \( y \) value of \( 3 \) and confirming that both paths lead to the same solution \( (-1, 3) \).